2021
DOI: 10.1021/acs.jced.1c00531
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Behavior of l-Arginine α-Ketoglutarate in Ten Pure and Two Binary Water + Ethanol and Water + Acetone Solvent Systems

Abstract: The solubility data of L-arginine α-ketoglutarate (AAKG) were determined by the static gravimetric method from 283.15 to 323.15 K in 10 pure solvents (water, methanol, ethanol, isopropanol, acetone, acetonitrile, dichloromethane, ethyl acetate, 2-butanone, and 1,4-dioxane) and two water + ethanol and water + acetone binary solvent systems. According to the experimental results, their solubility positively correlated with the temperature. In the selected solvent systems, there was no polymorph found. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…33 E T ( 30) is a physical property parameter considering the dielectric constant, dipole moment, and other physical properties, which can be used as a perfect empirical solvent polarity-scale reference. 34 It can be found that except for nbutanol and isobutanol, the solubility in polar protic solvents is in agreement with E T (30), and for the polar aprotic solvents, except for acetonitrile, ethyl acetate, and 1,4-dioxane, the solubility is positively correlated to E T (30) This shows that the solubility is the result of many factors and the polarity of solvents is not the only factor affecting the process of dissolution. 31,32,35 4.3.2.…”
Section: Powder X-ray Diffraction Resultsmentioning
confidence: 71%
“…33 E T ( 30) is a physical property parameter considering the dielectric constant, dipole moment, and other physical properties, which can be used as a perfect empirical solvent polarity-scale reference. 34 It can be found that except for nbutanol and isobutanol, the solubility in polar protic solvents is in agreement with E T (30), and for the polar aprotic solvents, except for acetonitrile, ethyl acetate, and 1,4-dioxane, the solubility is positively correlated to E T (30) This shows that the solubility is the result of many factors and the polarity of solvents is not the only factor affecting the process of dissolution. 31,32,35 4.3.2.…”
Section: Powder X-ray Diffraction Resultsmentioning
confidence: 71%